Electronic Health Records System Using IOT - et. al., Yaramala Sri Sarayu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Healthcare system is one of the important sectors in any country for its national income. Growing use of communication technology many countries have implemented e-health card system. At present there is no existing electronic health care system in India. It is essential to keep every patient’s history records. The point of this proposed e-Health card framework is to improve effectiveness, access of medicinal services administrations. Using the e-Health card all patient’s data, doctor’s prescription, patients present and previous health history which is stored using API can be accessed through a web page by the authorized parties using IOT. Our proposed thought conveys the benefits of secure medicinal services in India utilizing data and correspondence advancements. Digital records leave better tracking and more standardized documentation of patient interactions, which has the potential to scale back error. A patient may visit a hospital for treatment of a particular disease or illness and sometimes may have to be promoted to a hospital with better facilities and technological advancements, in such case a database which be accessed by every hospital is necessary, therefore our project aims on providing database and a web page which can accessed by all the hospitals.